Neutrophilic Epitheliotropism Is a Histopathological Clue to Neutrophilic Urticarial Dermatosis. (January 2016) - Broekaert, Sigrid M. C.; Böer-Auer, Almut; Kerl, Katrin; Herrgott, Ilka; Schulz, Xenia; Bonsmann, Gisela; Brehler, Randolf; Metze, Dieter
Abstract : Background: Neutrophilic urticarial dermatosis (NUD) comprises a particular autoinflammatory condition within the spectrum of aseptic neutrophilic dermatoses characterized by a distinct urticarial eruption clinically and a neutrophilic dermatosis histopathologically. Objective: In this study, we reviewed skin biopsies of lesional skin of patients seen in our outpatient clinic for autoimmune dermatoses and in allergy department from 1982 to 2014 that fulfilled these criteria. Methods: A total of 77 biopsies from 50 patients were analyzed histopathologically. Included were cases of Schnitzler syndrome, Still disease, systemic lupus erythematosus, Sjögren syndrome, cryopyrin-associated periodic syndrome, primary biliary cirrhosis, inflammatory bowel disease, and those that had signs of systemic inflammation not otherwise specified, that is, fever, arthritis, leukocytosis, and elevated erythrocyte sedimentation rate. A control cohort was defined as including a total of 70 biopsies from 50 patients comprising neutrophilic urticaria (pressure-induced and not pressure-induced), conventional urticaria, lupus erythematosus expressing neutrophils, and exanthematous drug reaction of macular type expressing neutrophils. Results: Skin biopsies of NUD revealed a perivascular and interstitial neutrophilic infiltrate focally extending into the epithelia of epidermis, hair follicles, sebaceous and sweat glands, a feature which we termed neutrophilic epitheliotropism. This neutrophilic epitheliotropism proved to be of high sensitivity (83.1%) and lower specificity (74.3%). The histological findings could be substantiated by immunohistochemical markers for leukocytes (elastase and myeloperoxidase), in particular in cases where neutrophils showed uncharacteristic band-like nuclei. Conclusions: Neutrophilic epitheliotropism is a new sensitive and specific histopathological clue for NUD, a histopathological reaction pattern within the spectrum of neutrophilic dermatoses that needs to be differentiated from conventional urticaria. Abstract : Supplemental Digital Content is Available in the Text.